Effects of intravenous glucose infusion and nutritional balance on serum concentrations of nonesterified fatty acids, glucose, insulin, and progesterone in nonlactating dairy cows - Vieira, F. V. R. [UNESP]; Lopes, C. N. [UNESP]; Cappellozza, B. I. [UNESP]; Scarpa, A. B. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2010)
The objective of this study was to evaluate serum concentrations of nonesterified fatty acids, glucose, insulin, and progesterone in nonlactating dairy cows according to nutritional balance and glucose infusion. Ten nonlactating, ovariectomized Gir x Holstein cows were stratified by body weight (BW) and body condition score (BCS) on d - 28 of the study, and randomly assigned to 1) negative nutrient balance (NB) or 2) positive nutrient balance (PB). From d -28 to d 0, cows were allocated according to nutritional treatment (5 cows/treatment) into 2 low-quality pastures with reduced forage availability. However, PB cows individually received, on average, 3 kg/cow per day (as-fed) of a concentrate during the study. All cows had an intravaginal progesterone releasing device inserted on d -14, which remained in cows until the end of the study. Cow BW and BCS were assessed again on d 0. on d 0, cows within nutritional treatment were randomly assigned to receive, in a crossover design containing 2 periods of 24 h each, 1) intravenous glucose infusion (GLU; 0.5 g of glucose/kg of BW, as a 5% glucose solution administered, on average, at 32 mL/min over a 3-h period), or 2) intravenous saline infusion (SAL; 0.9% solution infused on average at 32 mL/min over a 3-h period). Prior to the beginning of each period, all cows were fasted for 12 h. Blood samples were collected, relative to the beginning of the infusion, at -12 and -11.5 h (beginning of fasting), and at - 0.5, 0, 0.5, 1, 2, 3, 4, 5, and 6 h. Following the last blood collection of period 1, cows received (PB) or not (NB) concentrate and were returned to their respective pastures. Changes in BCS and BW were greater in NB cows compared with PB cows (-0.60 and -0.25 +/- 0.090 for BCS, respectively; -22.4 and 1.2 +/- 6.58 kg for BW, respectively). Cows receiving GLUC had greater glucose concentrations from 0.5 to 3 h relative to infusion compared with SAL cows. Insulin concentrations were greater in PB cows assigned to GLUC compared with SAL cohorts at 0.5 and 3 h following infusion, whereas NB cows assigned to GLUC had greater insulin concentrations compared with SAL cohorts at 0.5, 1, 2, and 3 h. Progesterone concentrations were greater in PB cows assigned to GLUC at 2, 3, and 4 h following infusion compared with SAL cohorts. In conclusion, the effects of glucose infusion on serum concentrations of insulin and progesterone in nonlactating dairy cows were dependent on cow nutritional status.
Keywords: glucose infusion; insulin; nutritional status; progesterone